Implementing the problem-based learning in order to improve the students’ HOTS and characters - Jailani Jailani; Sugiman Sugiman; Ezi Apino (Jurnal Riset Pendidikan Matematika, 2017)
The study was to describe the implementation of Problem-Based Learning (PBL) toward the improvement of students’ Higher Order Thinking Skill (HOTS) and characters and to describe the obstacles that had been encountered within the implementation. The study was a mixed research that made use of concurrent mixed method design. The population in the study was the students from eight junior high schools that had been selected from six provinces in Indonesia namely the Yogyakarta Special Region, Bengkulu, South Borneo, West Nusa Tenggara, Southeast Sulawesi and Papua. There were 648 students who had been selected randomly from these schools. The researchers conducted the PBL process within the experimental classes and the expository learning process within the eight control classes. The data gathering process was conducted through the test, the self-assessment and the open questionnaire. The quantitative data analysis was conducted inferentially using multivariate and univariate analysis, while the qualitative data analysis was conducted descriptively. The results of the study showed that: (1) the implementation of PBL had been more effective in comparison to the expository one in terms improving the students’ HOTS; (2) the implementation of PBL had not been more effective in comparison to the expository one in terms of improving the students’ characters; and (3) in overall the obstacles that had been encountered within the implementation of PBL process were related to the teachers’ unpreparedness, the time allocation, the unequal students’ input, the students’ learning habits and the difficult assessment.